Investigating The Impacts of Youtube Educational Vlogs on EFL Students’ Speaking Motivation - Raihan Fhonna (Journal of Innovation in English Education and Language Teaching, 2025)
This study investigates the impact of YouTube educational vlogs on the English-speaking motivation of students at UIN Ar-Raniry. Recognizing that many students struggle with speaking fluency and confidence due to limited practice and high anxiety, this research aims to explore whether digital tools, particularly educational vlogs, can serve as effective supplementary learning resources. The study applied a qualitative method, involving a questionnaire distributed to all 187 students of the batch of 2022 in the English Education Department to identify vlog users. From the respondents, five participants who regularly engaged with English educational vlogs and expressed motivation to improve their speaking skills were selected for in-depth interviews through purposive sampling. The findings reveal that educational vlogs significantly enhance students’ speaking motivation by providing consistent exposure to natural language, reducing speaking anxiety, and presenting language in a more engaging and relatable manner. Key features such as clear pronunciation, grammar explanations, real-life examples, and engaging visuals contribute to improved confidence and willingness to speak. The study concludes that YouTube educational vlogs are a valuable tool to support English-speaking development among students and recommends their integration into both independent learning and classroom.